The Role of Lymph Node Density in Predicting Survival Post-Cystectomy in Patients with Bladder Cancer; A Single-Center Retrospective Analysis - Alireza Lashay; Mostafa Farajpour; Masoumi, Navid (Archives of Men's Health, 2024)
Background: Lymph Node involvement in patients with bladder cancer directly affects their prognosis after cystectomy. With the advent of various extensions for lymphadenectomy during radical cystectomy, Lymph Node Density (LND) has been introduced as a stable measure to quantify the extent of LN involvement. This study evaluates the prognostic value of LND on the survival of these patients in our center. Methods: Our historical cohort reviewed the clinical records of 165 patients who underwent cystectomy at Modarres Hospital in Tehran, Iran during 2012-2018. The presence of positive LNs, the total number of positive LN, and LN density were evaluated for their effect on Overall survival (OS) and recurrence-free survival (RFS) at 3- and 5-years post-surgery. In addition, we assessed the impact of age, gender, type of diversion, P stage, lymphovascular invasion (LVI), location of involved LNs, ureteral involvement, positive surgical margin, and the presence of carcinoma in situ on patients’ survival. Results: According to ROC curve analysis, an LND cut-off point of 10.82 was calculated to predict patients’ survival (AUC:0.70, 95%CI: 0.496-0.691). An LND >10.82 significantly increased the risk of cancer-related death. Among all study variables, LND had the most prominent effect on OS (HR:2.49, 95% CI:1.3-4.4, P=0.002). For 3- and 5-year RFS, LVI had the highest impact (HR: 2.63, 95% CI: 1.3-5.1, P=0.005 and HR: 1.96, 95% CI: 1.2-3.0, P=0.002, respectively) Conclusion: Our analysis indicates that an LND >10.82 has the highest predictive potential for OS among the pathological features of patients undergoing cystectomy.